Impact of Rotational Grazing Systems on the Pasture Crop Coefficient for Irrigation Scheduling†. (11th January 2018) - KC, Birendra; Mohssen, Magdy; Chau, Henry Wai; Curtis, Andrew; Cuenca, Richard; Bright, John; Srinivasan, Ms; Hu, Wei; Cameron, Keith
Abstract: Crop coefficient ( K c ) estimations of ryegrass pasture ( Lolium perenne ) that matches the actual plant canopy represented by height ( h ) in rotational grazing systems have been assessed. This study investigated the impacts of grazing rotations on K c, using non‐weighing percolation lysimeters. The FAO Penman–Monteith equation was used to estimate the reference evapotranspiration (ETr ) from daily weather data. A water balance approach was applied to drainage data from 20 lysimeters to calculate actual evapotranspiration (ETa ). Based on ETa and ETr, K c was estimated for the different pasture growth stages of a grazing rotation. Results showed that K c and h can be modelled by a linear relationship. Pre‐ and post‐grazing pasture heights were typically 30 and 10 cm, respectively, for which estimated K c values were 1.0 and 0.6, respectively. Thus, due to variations in pasture height at different grazing stages, the conventional irrigation scheduling using a single K c of 1.0 does not take into account the dynamic water demand for rotationally grazed pasture. Irrigation scheduling that incorporates variations in K c with pasture growth stage will lead to more efficient water use and importantly less drainage and overland flow, perhaps the biggest environmental challenge for pastoral irrigators in New Zealand, without impacting on productivity. Copyright © 2018 John Wiley & Sons, Ltd.